Impacts of urbanization on water quality of Sungai Maong - Juhsep, Langi (Universiti Malaysia Sarawak (UNIMAS), 2005)
The assessment of water quality at Sungai Maong was carried out in terms of the physical, chemical and biological characteristics of the water body. In this project, the quality of the river water was determined using the Water Quality Index (WQI). Six parameters namely DO, BOD, COD, TSS, pH and NH3-N were used to compute the water quality index. The main objectives of this project are to classify Sungai Maong based on the WQI and to determine the impacts of urbanization on Sungai Maong water quality. River water sampled from Sungai Maong was tested three times and was compared between the dry and wet seasons. The WQI estimated during dry were much lower as compared to that during wet at all stations. Based on the WQI, certain sections of Sungai Maong were classified into designated classes. Three samplings were carried out at six stations along Sungai Maong. One of the sampling was done during the dry season and the other two were collected during the wet season. Seasonal variation of the water qual ity of Sungai Maong was assessed